Case report: Can a patient with an active cancer receive a kidney transplant?. Issue 3 (October 2019) - Buxeda, Anna; Pérez-Sáez, María José; Granados, Ana Marina; Redondo-Pachón, Dolores; Mir, Marisa; Barbosa, Francesc; Rodrigo, María Teresa; Sitges-Serra, Antonio; Pascual, Julio; Crespo, Marta
Introduction: An active cancer is an absolute contraindication for kidney transplantation and a frequent cause of wait-list patient exclusion for long periods. Waiting time for kidney transplantation after the cancer diagnosis/treatment depends on multiple factors such as type of cancer, stage, histological type, prognosis, and physicians' opinions. Case description: In this study, we describe a case of a 52-year-old man with medullary thyroid carcinoma classified as T1N1bM0 stage IV-A, who received a human leukocyte antigen identical living donor kidney transplantation despite not being biochemically cured. He received maintenance immunosuppression with tacrolimus, prednisone, and mycophenolic acid, switched to everolimus plus prednisone after 8 months. After 5 years, kidney function is excellent and there is no structural recurrence of the disease on imaging tests, although serum calcitonin levels remain elevated but stable. Conclusion: This is the first report that exposes the case of a patient with an active thyroid neoplasm receiving kidney transplantation. The good prognosis of the active neoplasm and the fact of having an identical human leukocyte antigen optimal donor made us proceed with the transplant with an excellent 5-year outcome.